The gamification of learning and instruction : game-based methods and strategies for training and education - Kapp, Karl M., 1967- (San Francisco, CA : Pfeiffer, 2012)
'Learning professionals are finding success applying game-based sensibilities to the development of instruction. This is the first book to show how to design online instruction that leverages the best elements of online games to increase learning, retention, and application. It explains how to match different game strategies to types of learning content for the right learning outcome and discusses how gamification techniques can be used in a variety of settings to improve learning, retention and application of knowledge. Supported by peer-reviewed studies and examples from corporations who have adopted game-based learning successfully, the book illustrates how combining instructional design thinking with game concepts can create engaged and interactive learning experiences across a variety of media, from online to face-to-face'--
Includes bibliographical references (pages 285-295) and index.
Keywords: Educational games; Simulation games in education; Computer-assisted instruction